Dynamics of innovation in European regions - Maria Manuela Natário; Jo\~ao Pedro Couto; Ascens\~ao Maria Braga; Teresa Maria Tiago (European Regional Science Association (ERSA), 2011)
There is interest in both academic literature and regional governments about the innovativeness of regions and the drivers of that competitiveness, especially if considering the impact on economic development and social progress. Innovation is the base for the global competitiveness. Innovative capacity enables regions to increase their productivity and attract investments, thereby sustaining continuous progress in the quality and standard of living. This study aims to measure regions' innovativeness in different European regions and to evaluate the nature of the innovation process and the relationship existing between its innovativeness' and its region of origin. It proceeds from the assumption that the competitiveness of a region is reflected in its innovation capacity or innovation dynamic. The literature review regarding regions' innovativeness produces some insights regarding to the effect of contextual elements on regions performance. Thus, the objective is to compare the European regions to verify the existence of subjacent clusters and find out the characteristics that distinguish the different group of regions. The innovative capacity is considered in terms of innovative output and several factors are analysed to identify and differentiate the dynamics of innovations of the regions. The results point to the existence of five groups of regions, and the factors identified are related to innovation process, namely forms of innovation, factors and objectives of innovation and with aspects related to the innovation framework such as tertiary education and life-long learning, business and public R&D expenses, and level of collaboration for innovating.
Keywords: 330